Pengaruh Culture Event di Anjungan Bengkulu Taman Mini Indonesia Indah Jakarta Terhadap Citra Destinasi Wisata Provinsi Bengkulu - Lestari, Annisa Asri; Waluya, Bagja; Andari, Rini (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
Bengkulu is one of the provinces in Indonesia, which has many potentials in terms of natural and cultural diversity. Looking at the numbers of potentials for cultural tourism around the province, Bengkulu Province was expected to increase the number of tourists for its unique characteristic and good image adhering in the minds of prospective tourists as a cultural destination. Problems occurred in Bengkulu Province is a fluctuating level of tourist visits to the province, and the growth level tends to be low. This is due to the image of Bengkulu Province as a tourist destination that is not good enough in the minds of prospective tourists. Hence, Anjungan Bengkulu, which is located in Indonesian Miniature Park, Jakarta was having the effort to overcome this problem. Therefore, the researcher chose Cultural Event as the solution that can be implemented to improve the Destination Image of the province. On this study, the independent variable (X) was Cultural Event, consisting of Spectacularisation, Theme, Participation and Immersion. The dependent variable (Y) was Destination Image. The type of the research used was a descriptive explanatory survey, and supported by the cross-sectional method. The samples in this study were 108 respondents consisting of individual visitors at the Anjungan Bengkulu Cultural Event, the sampling technique used was purposive sampling. Data analysis technique employed was multiple regressions. The result showed that the implementation of Cultural Event at Anjungan Bengkulu was assessed in the high category, with a dimension of "Spectacularisation" received highest score, and the lowest one was the "theme". Subsequently, visitors’ response regarding Destination Image at Anjungan Bengkulu was also categorized in a very high level, with a dimension of cognitive image received highest score and dimension of affective image became the lowest one. Results showed that there is a significant influence between Culture Event and Destination Image.